A remote optically controlled hydrolase model based on supramolecular assembly and disassembly of its enzyme-like active site. Issue 8 (11th February 2019) - Ma, Ningning; Li, Fei; Li, Siyuan; Chu, Shengnan; Han, Lili; Liu, Shengda; Yan, Tengfei; Tian, Ruizhen; Luo, Quan; Liu, Junqiu
Abstract : A photoresponsive hydrolase model was constructed by supramolecular self-assembly to study the structure-related catalytic behaviors at different morphological transition stages. Abstract : A photoresponsive hydrolase model was constructed through the spatial organization of histidine/arginine-containing peptide supra-amphiphiles that are held together by cucurbit[8]uril (CB[8]) methylviologen (MV) azobenzene (Azo) ternary complexation and subsequently self-assemble into highly uniform giant vesicles. The reversible morphological transition of the vesicular structures to non-assembled peptide fragments was triggered by azobenzene photoisomerization. This enables the assembly/disassembly of its enzyme-like active site to cause a dramatic change in hydrolytic activity. The dynamic process can be directly monitored to determine the supramolecular structure-related enzymatic parameters, which may help to understand how the regulation of enzyme activity is coupled to the aggregation behaviors of natural enzymes.